Vocational High School Quality Viewed from Teacher Competencies - Yat Wawan lolo (Universitas Negeri Makassar, 2018)
ABSTRACTThis study aims to describe the competence of productive teachers of Vocational High School in North Morowali Regency in terms of four teacher competencies. This research is a descriptive study, conducted in four accredited Vocational High Schools in North Morowali District. The respondents were 178 students. Data were collected through documentation and questionnaires. Data were analyzed descriptively by display in the form of data categories and graphs. The results showed: (1) pedagogic competence of teacher equal to 66,76% with high category, professional competence of teacher equal to 77,92% including high category, teacher personality competence equal to 78,66% including high category, teacher social competence equal to 79,82 % including high category.Keywords: teacher, vocational, competence